(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2023)
In radiology, knowing the X-ray spectrum characteristics makes it possible to estimate the absorbed dose in the patient and to improve image quality. In this study, an X-ray generator was proposed using the MCNPX code and to validate it, the simulated spectrum was compared to the data provided from AAPM Task Group 195, which resulted in a percentage difference of 8.7%. Furthermore, several X-ray spectra were generated and compared to the spectra obtained from commercially available softwares as xpecgen and SpekCalc. The percentage differences were of the order of 13% in comparison with SpekCalc and 8% with xpecgen. The major differences obtained between those spectra were concentrated in the region of characteristic peaks, independently if variations in electron beam energy, target angle or filtration thickness were performed.